2003
DOI: 10.1007/s10350-004-7282-x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability and Mutations in DNA Mismatch Repair Genes in Sporadic Colorectal Cancers

Abstract: The results indicated that a germline mutation of DNA mismatch repair gene was a rare event in sporadic colorectal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 38 publications
0
30
2
1
Order By: Relevance
“…Disease recurrence was detected by sonographic ultrasound, computed tomography, or magnetic resonance imaging, and was confirmed by pathologic examination. The microsatellite instability status of 230 of the enrolled cases had been previously reported (15); two cases were additionally analyzed for microsatellite instability at the BAT-25 and BAT-26 markers as previously described (15).…”
Section: Methodsmentioning
confidence: 99%
“…Disease recurrence was detected by sonographic ultrasound, computed tomography, or magnetic resonance imaging, and was confirmed by pathologic examination. The microsatellite instability status of 230 of the enrolled cases had been previously reported (15); two cases were additionally analyzed for microsatellite instability at the BAT-25 and BAT-26 markers as previously described (15).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown here that only 17% of tumors were MSI-H, an incidence similar to the 12 to 18% prevalence in sporadic colorectal cancer (3,22) and significantly lower than reported in HNPCC and patients with suspected HNPCC (5,23,24). BAT26 was used as the basis of a study on a limited assay that showed MSI-H rate as 9% in the 230 unselected cases of Korean sporadic colorectal cancer (25). Approximately 70% of 24 markers in our study accurately identified MSI-H, indicating that these markers could be applied to identifying these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of MSI-H in Korean endometrial cancer patients is higher than the 9.3% reported in primary sporadic CRC in Korea, 17 and similarly, our finding that 23% of endometrial tumor samples showed loss of MMR protein expression indicates that this rate is higher than the 8.6% seen in primary sporadic CRC in Korean patients. 18 We performed mutational analyses of patient samples from the identified clinical HNPCC, s-HNPCC and selected patients who showed both MSI-H and loss of MMR protein expression. Overall, the mutation rate in clinical HNPCC patients was 50% (2/4), and that in the s-HNPCC patients was 12.5% (1/8).…”
Section: Discussionmentioning
confidence: 99%